Efficacy and safety of the first-line systemic treatments in patients with advanced-stage urothelial carcinoma: a systematic review and network meta-analysis - Zhao, Yang; Xu, Xiaoqing; Sun, Yuhan; Yu, Xinyang; Qi, Yuanfu (Frontiers in Oncology, 2024)
IntroductionIn recent years, some clinical studies of first-line treatment for advanced-stage urothelial carcinoma (aUC) have reached the main endpoint, showing inconsistent clinical efficacy. We hope to explore the efficacy and safety of first-line treatment for aUC.MethodsThe relevant literature from January 2000 to February 2024 was searched, and the R language (version 4.3.1) was used to perform a network meta-analysis based on the JAGS package and GEMTC package under the Bayesian framework. The main indicators included OS, PFS, ORR and adverse events of grade 3 or higher. This study has been registered in PROSPERO (CRD42024525372).ResultsA total of 8 RCTs involving 5539 patients and 12 treatments were included. Pembrolizumab plus Enfortumab Vedotin (PEM+EV) was significantly better than other groups in OS, PFS and ORR. In terms of OS, PEM+EV was significantly better than nivolumab plus platinum-based chemotherapy (NIVO+platinumCT) (HR=0.60; 95% CI: 0.45-0.81), PEM+platinumCT (HR=0.55; 95%CI: 0.42-0.72), atezolizumab (ATE) + platinumCT (HR=0.57; 95%CI: 0.43-0.75) and platinumCT (HR=0.47; 95%CI: 0.38-0.58). In terms of PFS, PEM+EV was also significantly better than NIVO+platinumCT (HR=0.62; 95%CI: 0.48-0.82), PEM+platinumCT (HR=0.58; 95%CI: 0.45-0.74), ATE+platinumCT (HR=0.55; 95%CI: 0.43-0.69) and platinumCT (HR=0.45; 95%CI: 0.38-0.54). In terms of ORR, PEM+EV had a significant be nefit compared with other treatment measures, which was 2.63 times that of platinumCT (OR=2.63; 95%CI: 2.00-3.45). The adverse events of grade 3 or higher in immunotherapy (ATE, PEM, durvalumab) was significantly lower than other treatment measures.ConclusionsPEM+EV can significantly prolong OS and PFS compared with other treatments, and has a higher ORR. The adverse events of grade 3 or higher of ATE was the lowest.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024525372, identifier CRD42024525372.